Mevsimlik Tarım İşçisi Gençlerin Sağlıklı Yaşam Bilgi ve Davranışlarına Akran Eğitiminin Etkisi/The Effect of Peer Education on the Healthy-Life Knowledge and Behavior of Young Seasonal Farmworkers - Zeynep Simsek; Evin Kırmızıtoprak (Turkish Society of Public Health Specialists, 2013)
Objective: To evaluate the effects of peer education on young seasonal farmworkers' healthy life knowledge and behavior related to living arrangement, pesticide use, and reproductive - sexual health. Method: In this controlled-experimental design study, two settlements with similar characteristics were selected experiment and control group. Twenty six youths from experimental area were selected and trained as peer educator. One-hundred young people from among the 650 in that neighborhood that received training were randomly selected and compared with the control group, which consisted of 125 youths. For data collection, a questionnaire developed by the authors was used. The questionnaires were applied in face-to-face interview. A total of 113 young people were reached in the intervention group (response rate 90%), and 118 young people were reached in the control group (response rate 94%). It was used t-test, chi-square and analyses of variance for statistical analyses. Findings: No significant differences were detected between the intervention and control groups with regards to age, gender, duration of work as farmworkers or level of education (p>0.05). The difference between the total scores of the intervention and control groups (respectively;50.8±8.6- 27.2±9.1) and the scores of sub domains were significant (p<0.05). In addition, the frequency of use of iodized salt, vaccination, hand-washing, breast self examination and testicular self examination was significantly higher in the intervention group. Conclusion: The peer education model could be of use in the development of healthy life skills among young seasonal farmworkers.